The housekeepers ebook A novel. - Hay, Alex (2023)
The night of London's grandest ball, a bold group of women downstairs plot a daring revenge heist against Mayfair society in this dazzling historical novel about power, gender, and class Named a Best Book of Summer by The Washington Post * Good Housekeeping * Harper's Bazaar * Reader's Digest "Rollicking fun and entirely original... Anyone who relishes a good party gone wrong will devour this." —Sarah Penner, New York Times bestselling author of The Lost Apothecary Mrs. King is no ordinary housekeeper. Born into a world of con artists and thieves, she's made herself respectable, running the grandest home in Mayfair. The place is packed with treasures, a glittering symbol of wealth and power, but dark secrets lurk in the shadows. When Mrs. King is suddenly dismissed from her position, she recruits an eclectic group of women to join her in revenge: A black market queen out to settle her scores. An actress desperate for a magnificent part. A seamstress dreaming of a better life. And Mrs. King's predecessor, with her own desire for vengeance. Their plan? On the night of the house's highly anticipated costume ball—set to be the most illustrious of the year—they will rob it of its every possession, right under the noses of the distinguished guests and their elusive heiress host. But there's one thing Mrs. King wants even more than money: the truth. And she'll run any risk to get it... After all, one should never underestimate the women downstairs. "A deliciously clever novel... You'll never have so much fun cheering on grand larceny." —Nina de Gramont, New York Times bestselling author of The Christie Affair, a Reese's Book Club Pick *Don't miss Alex Hay's clever next novel, The Queen of Fives, in which a mysterious heiress with a secret sets her sights on London's biggest wedding of the season